การดื่มเครื่องดื่มชูกำลังของผู้ใช้แรงงานในตำบลต้นธง อำเภอเมือง จังหวัดลำพูน - จิราภรณ์ เสวะกะ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purposes of this descriptive study were to investigate the consumption of energy drink among workers in Tonthong Sub-district , Mueang District, Lamphun Province and to compare the amounts of caffeine and sugar that they obtained from drinking energy drinks. The data form 264 workers out of 2,587 people were collected from four villages (66 workers each) and were studied using the estimating a finite population proportion formula and multi-stage random sample (multi-stage sampling). Information that were collected using a questionnaire general information, illness history, working conditions, smoking, alcohol and energy drinks consumption habit. All the samples took the respondent on their own. The data was analyzed using descriptive statistics including frequency distribution, percentage, mean and standard deviation, as well as correlation analysis by Chi-Square and Fisher's exact Test. The results showed that more than half of the samples were female (53.8%) between the ages of 50 - 60 years old (64.0%), married (78.8%), and completed elementary level education (70.1%). Almost half of samples work daily (47.3%), others work 7-8 hours per day (50.4%), Percentages of workers that smoke and drink alcohol were 12.5% and 26.5% respectively. The most consumed beverage in addition to energy drinks is coffee (67.8%), and cola (28.8 %), Half of the workers with diabetes and high blood pressure cannot always control their chronic symptoms (51.1%). Half of the samples consume energy drinks (50.4%), mostly for a period of 4 - 6 years (43.6%). About 12.8% have been drinking for more than 10 years. As high as 13.5% drink every day, mostly one bottle per day (94.0%) at the frequency of 3 days per week (32.3%). Most people drink every time they work (62.4%), and more than half of these drink before work (51.1%). Pattern of drinking is to mostly to drink it out of bottles (92.5%), without mixing anything (94.7%), while a few mixed with alcohol (3.8%). The main reason of drinking is to get rid of sleepiness (69.9%), and to stimulate and rejuvenate the body (53.4%). Highest average amount of caffeine obtained per day from drinking energy drink was found in diabetes risk group labors at 54.8 mg, followed by the hypertension group at 54.7 mg, the diabetes group at 53.3 mg, and the normal group at 52.6 mg. For the sugar content obtained per day from drinking energy drinks, the highest amount was found in the hypertension risk group at 27.2 g, followed by the diabetes group at 26.2 g, the diabetes risk group at 26.1 g and the normal group at 24.9 g. From the analysis of the relationship between personal factors and energy drink drinking habit, it was found that gender, number of working days per week, number of working hours per day, chronic illness, smoking and alcohol consumption habit have significant effect at the 0.05 level. Relevant authorities should continuously monitor energy drink consumption habit among workers. Calculation for the daily amount of caffeine and sugar obtained from energy drinks consumption should be publicized. This will promote workers to calculate their own caffeine and sugar consumption from energy drinks.